Intermittent Theta-Burst Stimulation Over the DorsoLateral PreFrontal Cortex (DLPFC) in Healthy Subjects Produces No Cumulative Effect on Cortical Excitability - Bouaziz, Noomane (Front Psychiatry, 2021)
Background: Intermittent Theta Burst Stimulation (iTBS) is a design of repetitive Transcranial Magnetic Stimulation (rTMS) and could be a candidate to replace rTMS in the treatment of depression, thanks to its efficacy, shorter duration, and ease of use. The antidepressant mechanism of iTBS, and whether this mechanism is mediated by a modulation of cortical excitability, remains unknown. Methods: Using a randomized double-blind, sham-controlled trial, 30 healthy volunteers received either iTBS or a sham treatment targeting the left DorsoLateral PreFrontal Cortex (L-DLPFC), twice a day over 5 consecutive days. Cortical excitability was measured before and after the 5 days of stimulation. Results: No difference in cortical excitability was observed between active or sham iTBS. Conclusion: Our study does not support any effect on cortical excitability of repetitive iTBS targeting the L-DLPFC.